Cultural and Art Discourse in Modern Malay Poetry by Kelantanese Poets - Ab Rahman, Norhayati (Malay Literature; Vol 35 No 1 (2022): Malay Literature Volume 35 Number 1 June 2022, 2022)
Kelantan is one of the states that has produced many writers with some of them have achieved success at the national level. Apart from being the Serambi Mekah due to the tradition of intellectualism inherited from hundreds of years ago, Kelantan is also often referred to as the ‘depth of poetry’ because many poets were born in this state. Along with that, there is a perception that Kelantan poets express feelings and thoughts related to the famous culture and artistic heritage in the state of Kelantan. Thus, this study aims to identify the aspects of documentation and cultural and art discourse shown in the poetry, as well as to analyze the forms of cultural and artistic discourse presented in poetry by selected Kelantan poets using the concept of culture. For that purpose, this study will use data in the form of poems by Kelantan poets such as A. Aziz Deraman, Azmi Yusoff, Ezani Haji Daud, Mazli Husma, Wanrazuhar, Rosli K. Matari, and Rahimidin Zahari. The results of this study show that various aspects of culture and art are discoursed in poetry by Kelantan poets, including the aspects of language, the use of dialect, interest in Jawi inscription, traditional games, and shadow play. The findings of this study also prove that Kelantan poets show a significant tendency in the discourse on cultural and artistic aspects in their works.